Pengetahuan dan Sikap Masyarakat di Daerah Endemis Filariasis Limfatik (Studi Kasus Kabupaten Sarmi, Papua) - Rustam, Muh Zul Azhri; Sipayung, Mina (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2018)
District Sarmi is one of the districts in Papua which has the highest rate of microfilaria (mf) (47.06%) up to the year 2012. Province Papua filarial worm is Wuchereria bancrofti and is transmitted through the bite of a mosquito vector. The study aims to analyze the influence of community knowledge and attitudes towards the incidence of lymphatic filariasis in endemic areas in Sarmi District. This study used a case-control method. Samples comprised 32 case samples (mf +) and 32 control samples (mf-). The results of this study there was an influence between knowledge of Lymphatic Filariasis Incidence and no influence between attitudes toward lymphatic filariasis Incidence in Sarmi district. Proven by logistic regression test p-value of knowledge (0.019) and attitudes (0.389). According to the results of research and recommendations for lymphatic filariasis, the prevention system is health promotion, community development and training of health workers. Conclusions: Highest gender characteristics was male, adult, level of education from elementary school, the respondents worked as farmers and had low-income levels.Â Keywords: Lymphatic Filariasis, Knowledge, Attitudes.